The Effect of Workload and Employee Work Environment on Employee Job Satisfaction in Community Institutions Class Iia Serang - Irvan Setiawan; Kemal Taufik; Sri Wahyuningsih (Dinasti International Journal of Management Science, 2026)
This research has the following research objectives to determine the effect of workload on employee job satisfaction, to determine the effect of work environment on employee job satisfaction and to determine the effect of workload and work environment simultaneously on employee job satisfaction. The calculated t value of the workload variable (X1) is 5.242 which is greater than the t table value of 1.993 at a significance level of 5%. Thus, the hypothesis stating that workload has an effect on employee job satisfaction is accepted, the calculated t value of the work environment variable (X2) is 6.716 which is greater than the t table value of 1.993 at a significance level of 5%. Thus, the hypothesis stating that the work environment influences employee job satisfaction is accepted. The F test (ANOVA) results show that the calculated F value of 69.414 is greater than the F table value of 2.73, with a significance level of 0.000 <0.05. Thus, the hypothesis stating that workload and work environment jointly influence employee job satisfaction is accepted. The coefficient of determination (R²) value of 0.665 indicates that 66.5% of the variation in employee job satisfaction can be explained by the workload and work environment variables simultaneously. Meanwhile, the remaining 33.5% is influenced by other factors not examined.